PENGEMBANGAN SELF-HELP BOOK TEKNIK SELF-COMPASSION UNTUK MEMPERKUAT RESILIENSI AKADEMIK MAHASISWA TINGKAT AKHIR - Wisnu Arya Kusuma; Evi Afiati; Siti Muhibah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research aims to develop and test the feasibility of a self-compassion-based self-help book to strengthen the academic resilience of final-year students at the Faculty of Teacher Training and Education (FKIP), Sultan Ageng Tirtayasa University (UNTIRTA). Utilizing the Research and Development (R&D) method with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), the study began with an analysis showing that the majority of respondents possessed a moderate level of academic resilience and required supporting media. The development phase involved designing self-compassion materials and practical steps, followed by feasibility testing by experts in material, media, and language. Validation results indicated a feasibility rate of 91% for material, 73% for media, and 96% for language, categorized overall as "highly feasible." A limited trial on 10 students with low resilience yielded a product feasibility percentage of 94.16%. Based on these results, it is concluded that this self-compassion-based self-help book is highly feasible for implementation as an adaptive self-solution for final-year students in facing various academic challenges during the thesis writing process.